Characterization of amorphous niobium silicates powders synthesized by polymeric precursor method - Bertolini, M. J.; Zaghete, M. A.; Gimenes, R.; Paiva-Santos, C. O. (Elsevier B.V., 2005)
In this paper 4.5SiO(2)-3Al(2)O(3-x)Nb(2)O(5)-2CaO powders have been synthesized using a chemical process the Polymeric Precursor Method. The process of glass formation has been investigated by XRD and DTA, the results confirm that the prepared powders are glasses. Experimental data show that amount of Nb2O5 had a considerable effect on the T-g values. The structures of glasses prepared. have been determined by Si-29 and Al-27 MAS NMR and the results indicated that the network is formed by SiO4 and AlO4 tetrahedral linked and probably Si-O-Nb bonds are present in the vitreous network. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: niobium; glasses; polymeric precursor method